Analysis of Legal Protection for Debtors Regarding The Position of Using Standard Contracts in Relation To The Principle of Freedom of Contract on Bank Credit Agreement - Miswanto, Sidik; Ummu Adillah, Siti (TABELLIUS: Journal of Law, 2024)
This research is about "Analysis of Legal Protection for Debtors Regarding the Position of Using Standard Contracts in Relation to the Principle of Freedom of Contract" aimsto know and analyze legal protection for debtors against the position of using standard contracts in relation to the principle of freedom of contract in bank credit agreements, obstacles and how to overcome them. This study uses a sociological legal approach. Data collection is carried out through observation, interviews, literature studies and documentation. Data analysis is carried out descriptively qualitatively. The results of the study indicate that legal protection for debtors against the use of standard contracts in relation to the principle of freedom of contract in bank credit agreements includes preventive protection in the form of legal protection from the legal aspects of the agreement as stipulated in Article 1338 paragraph (1) of the Civil Code and Article 1320 of the Civil Code, aspects of consumer protection in Article 18 Paragraph (1) Letter g and letter h of the UUPK, which regulates restrictions on the use of standard clauses in credit agreements, as well as repressive protection in the form of dispute resolution options. Standard agreements have violated the principle of freedom of contract because when there is an imbalance regarding the burden imposed on the parties in the form of transferring obligations to the weaker party, the weaker party no longer has freedom, even though the principle of freedom of contract provides a guarantee of freedom to a person in matters relating to the agreement. However, in fact, if a standard agreement or contract does not violate the principles contained in an agreement or contract, then it is not a problem because in essence a standard agreement or contract is also a normal agreement or contract, the only difference is that a standard agreement or contract is provided by a party in a stronger position and cannot be changed even if the other party in the agreement wants a change or feels disadvantaged. The obstacles faced in the use of standard contracts in bank credit agreements are the prohibition on the use of standard clauses that have the potential to harm debtors or customers and the problems in the implementation of the credit agreement, namely problematic credit to bad credit. The way to overcome this is that the creation of a bank credit agreement that uses a standard contract must be carried out in accordance with the provisions of laws and regulations and strict credit analysis.